VD_FINDINFO HC / 2011 / 241 vom 12. Mai 2011 - VD Tribunal cantonal (2011)
CONVENTION SUR LES RELATIONS PERSONNELLES CONCERNANT LES ENFANTS, RELATIONS PERSONNELLES | 134 al. 2 CC, 273 CC, 274 CC, 241 CPC (CH), 308 al. 1 let. b CPC (CH)